2002
DOI: 10.1007/bf03191902
|View full text |Cite
|
Sign up to set email alerts
|

Speech recognition interface to a hospital information system using a self-designed visual basic program: Initial experience

Abstract: Speech recognition (SR) in the radiology department setting is viewed as a method of decreasing overhead expenses by reducing or eliminating transcription services and improving care by reducing report turnaround times incurred by transcription backlogs. The purpose of this study was to show the ability to integrate off-the-shelf speech recognition software into a Hospital Information System in 3 types of military medical facilities using the Windows programming language Visual Basic 6.0 (Microsoft, Redmond, W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
9

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 11 publications
2
23
0
9
Order By: Relevance
“…This technical difficulty could explain why radiology residents do not usually prefer this method for report generation. However, several studies have reported that speech recognition technology reduces the documentation time and cost and report turnaround time [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…This technical difficulty could explain why radiology residents do not usually prefer this method for report generation. However, several studies have reported that speech recognition technology reduces the documentation time and cost and report turnaround time [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Die Mehrheit der Studien, welche mögliche zeit-und kosteneinsparende Eigenschaften der medizinischen Spracherkennung un-tersuchten, weisen auf eine signifikante Reduktion der Bearbeitungszeit für die medizinische Dokumentation [7], [8], [9], [10], [11], [12], [13], [14], [15], [16] [19], [20] oder es konnte kein signifikanter Effekt gemessen werden [21], [22]. Die Kosten und Zeitersparnisse bei Verwendung der Spracherkennung konnten hier lediglich im Vergleich zum Diktat, durch den Wegfall der Notwendigkeit einer Schreibkraft, identifiziert werden [7], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18]. In den Studien, in denen die Spracherkennung mit der Texteingabe verglichen wurde, war kein [22] oder ein negativer Effekt des Einsatzes der Spracherkennung zu beobachten [19].…”
Section: Zeit-und Kostenanalyseunclassified
“…Nur wenige Autoren gehen aber auf den spezifischen Workflow des Befundungsprozesses in Lehr-und Universitätskrankenhäusern ein [15,17]. Innerhalb einer krankenhausweit implementierten KIS-RIS-PACS-Umgebung beinhaltet die RTT im Wesentlichen die Latenz zwischen Untersuchungsende und Befunderstellung (PACS Workload Queue), die Dauer der Befunderstellung sowie die Latenz zwischen Ende des Befundungsvorgangs (fertig gestelltes Diktat) und im RIS/KIS verfügbarem, korrigiertem radiologischen Befund (Transcription Queue) [15].…”
Section: Introductionunclassified
“…Die durchschnittliche RTT fällt auf ein Drittel bis ein Viertel des Ausgangswertes[15,19].Befundverfügbarkeit nach Einführung des SES. Der für CR und CT festzustellende Shift der kumulativen Befundverfügbarkeit zugunsten der ersten Stunden nach Untersuchungsende (Maximum der verfügbaren Befunde in der 2.…”
unclassified